The effect of combination of Carbopol 934P and 940P with Metolose 90SH-4000, 90SH-15.000 and 90SH-100.000 to the adhesive strength of mucoadhesive granules on stomach and intestine - Teti Indrawati; Goeswin Agoes; Elin Yulinah; Yeyet Cahyati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Sustein release dosage form with mukoadhesive system in stomach is a drugs delivery system that can increase bioavailability. The study was conducted the effect of polimers combination to mucoadhesive strength. Granules prepared by dry and wet granulation using the combination of Carbopol 934P and Carbopol 940P with Metolose 90SH-4000, Metolose 90SH- 15.000 and Metolose 90SH-100.000. Granules adhesive strength on stomach and intestinal mouse was investigated by mucoadhesive and wash off test. The results indicated that all of the mucoadhesive granules that prepared by wet and dry granulations could completely adhere on stomach and intestine in 5 minutes. Mucoadhesive strength on stomach and intestine of a single polymer was better than that of combinations of polymers. The strongest adhesion on stomach showed by Carbopol 940P and Metolose 90SH-15.000 combination (40 : 20).Key word : Adhesive, mucoadhesive granules.